»Svet čudovite lahkosti zvenenja sodobne glasbe« - Barbo, Matjaž (Muzikološki zbornik, 2022)
The article examines the activities and influence that the Slovenian society for new music Muzina had on the perception of contemporary music. The aesthetic coordinates of the society are connected with the contemporary international trends. At the same time, the activities of the society are presented in the context of the development of music in Slovenia in recent decades.
Keywords: contemporary music; društvo Muzina; glasbena društva; history of musical reception; Jež Brezavšček, Brina; Muzina Society; obletnice; recepcijska zgodovina; Slovenian music; slovenska glasba; sodobna glasba